2021
DOI: 10.34659/2021/4/28
|View full text |Cite
|
Sign up to set email alerts
|

Eco-innovation development in selected European and Asian countries: a comparative analysis

Abstract: The development of eco-innovation is driven by globalisation processes, technological progress and climate change. It is also directly related to the pursuit of sustainable development, as well as to the reduction of negative impacts on the environment and the efficient use of natural resources. Monitoring progress towards sustainable development requires the systematic measurement of eco-innovation. An important theoretical and practical challenge is to develop methods and indicators to measure eco-innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the authors indicated that the policy objectives of raw materials should be based on an assessment of their potential economic, social, and environmental impacts. They also emphasised that the priority of the European Union is to improve the efficiency of resource management and that resource assessment may be crucial from the point of view of other EU policies, including those related to eco-innovation and competitiveness (Urbaniec & Tomala, 2021). In addition, resource efficiency will enable the identification of resources of key importance to the EU economy, the use of which should be optimised through consumption reduction, recycling and substitutability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the authors indicated that the policy objectives of raw materials should be based on an assessment of their potential economic, social, and environmental impacts. They also emphasised that the priority of the European Union is to improve the efficiency of resource management and that resource assessment may be crucial from the point of view of other EU policies, including those related to eco-innovation and competitiveness (Urbaniec & Tomala, 2021). In addition, resource efficiency will enable the identification of resources of key importance to the EU economy, the use of which should be optimised through consumption reduction, recycling and substitutability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The environment in Poland is threatened by factors related to agricultural activities like a way of farming, land use, the nature of livestock production, and drainage system, as well as factors unrelated to agricultural activit-ies like emissions from enterprises' production and processing, residential buildings, waste management, sewage system, public transport, etc. (Urbaniec & Tomala, 2021). Every economic activity has certain effects on the environment, which can be more or less harmful, sometimes even irreversible.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…In the scientific literature, the concept of eco-innovation is investigated mainly from two perspectives. First, scientific literature investigates eco-innovation and considers eco-innovation as a tool for economic and financial growth, gaining competitive advantage, improving environmental performance, and sustainable development from the country-level perspective (Urbaniec & Tomala, 2021); industrylevel (Ullah et al, 2022); or firm-level (Zameer et al, 2022). Thus, given the aim and formulated problem, the primary focus of this dissertation is the firm-level environment.…”
Section: Eco-innovation Observatory 2012mentioning
confidence: 99%
“…Finally, Martínez-Ros and Merino (2023) found that eco-innovation provides an extra capability that enhances the probability of entering new international markets and that its effects are long-term. To sum up, eco-innovation plays an overwhelming role in internationalization and is considered a driver (direct or mediator) of internationalization, which improves the international performance of the firm and opens new market opportunities Urbaniec & Tomala, 2021). Therefore, this dissertation adopts the second approach, and the eco-innovation strategy is considered an integral component of the internationalization strategy.…”
Section: Strategic Decision-making Perspective On Eco-innovation Stra...mentioning
confidence: 99%